(untitled) - Starfield, Barbara (New York, 1998)
In Primary Care: Balancing Health Needs, Services, and Technology, Barbara Starfield presents evidence of the positive impact of primary care on the health of populations and provides innovative methods to evaluate the attainment and contribution primary care systems and practitioners. This volume is a valuable extension of the author's 1992 book on primary care, underscoring two additional areas: the role of primary care in facilitating equity in health services, and the emerging overlap between clinical medicine and public health. As primary care increasingly informs health care decision-making throughout the world, this updated edition is critical for the future trajectory of health policy.
Keywords: Chăm sóc y tế,Medical care